PERTAMBAHAN ALAMI (NATURAL INCREASE) TERNAK SAPI BALI DI KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Albartina Lumatalale; Isak P. Siwa; Feronica Parera (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2021)
The objective of this study was to known the natural increase of Bali cattle in sub-distirct of Kairatu, West Seram Regency. A survey method was applied and respondents were determined with purposive sampling. Respondent charateristics and specific variabels were observed as the study variabels. The first include farmer age, education level, main occupation, livestock purpose, business length, livestock resources, status and ownership. The next parameter consist of (1) population structure, (2) reproductive potential of cow, i.e. conception rate, calving rate, calving interval, weaning age, pre weaning mortality rate, and (3) natural increase. The result showed that the natural increase of Bali cattle was 17.69% or classified as moderate category.